FoMO: Kecemasan Digital di Kalangan Pengguna TikTok - Darmayanti, Dyan Paramitha; Arifin, Iqbal; Inayah, Muh (Universitas Muslim Maros, 2023)
TikTok is one of the most popular social media today and has even become one of the social media that triggered the emergence of fear of missing out (FoMO) phenomenon. FoMO is a feeling of anxiety, discomfort, and restlessness felt by a person when he/she feels missing out on opportunities, experiences, or even interesting events presented by other TikTok users. While the existing literatures mostly focuse on the psychological aspects of FoMO and the reasons behind its occurrence, a novel contribution of this article is the different levels of FoMO experienced by those who experience it. Using a qualitative approach, this study was conducted between May 2023 and August 2023. There were ten participants involved in this study who had experienced or were currently experiencing FoMO. They varied in terms of gender (four males and six females) and age (between 18 and 24 years old), status (six university students, two employees and the other two high school students. Data were collected using in-depth interview and observation. The research shows that FoMO is the fear of something happening and going viral on TikTok, but when someone misses it or experience it, then he/she will feel left behind, which is popularly termed as